Competence Interpertations of Religious Court For Islamic Family Law in Indonesia - Ruslin Ruslin (Alliance of Health Activists (AloHA), 2019)
Limitation study area in this article is the starting point of three scholarly foundations, the foundation of ontology related to the object of study, epistemological ground with regard to the method used in the study and axiology related to foundation with the purpose or significance of the study. The object of study in this article is the competence of the Religious Court in the interpretation of Islamic family law in Indonesia, covering permasalahan Interpretation of Family Law Islamic Religious Courts Indonesia, procedures Interpretation of Family Law Islamic Religious Courts Indonesia, judgment of Religious Courts in Indonesia there Interpretation Law and competent in the interpretation of Islamic Family Law in Indonesia Religious Courts. The method used, the study included a kind of normative legal studies approach to the blade, then the method of analysis, there are three, namely: (1) political approach, (2) statue approach, (3) analytical approach. The data source materials normative, ie competence Religious Courts of Indonesia and all sources of Islamic family law that is set in the regulations and legislation arranged in hierarchical.Techniques are Data collections to study for the document. This study, including qualitative assessment of normative, the analytical descriptive analysis (explanatory). Theoretical framework used, ie at the level of grand theory using the theory of ijtihad, the middle level of theory using the theory of law and society and on the plains applied theory using the theory of Islamic Sharia Judical system. While the significance of this study is to find the source of the law, the legal function and purpose of law. The results in the study which were to find the nature of legal interpretation procedures, problems that are interpreted in the Religious and who are competent to interpret the Islamic family law in Indonesia Religious Courts. Keywords: interpretation; Islamic family law; justice religion